2021
DOI: 10.3389/fmicb.2021.631885
|View full text |Cite
|
Sign up to set email alerts
|

Soluble, Colloidal, and Particulate Iron Across the Hydrothermal Vent Mixing Zones in Broken Spur and Rainbow, Mid-Atlantic Ridge

Abstract: The slow-spreading Mid-Atlantic Ridge (MAR) forms geological heterogeneity throughout the ridge system by deep crustal faults and their resultant tectonic valleys, which results in the existence of different types of hydrothermal vent fields. Therefore, investigating MAR hydrothermal systems opens a gate to understanding the concentration ranges of ecosystem-limiting metals emanating from compositionally distinct fluids for both near-field chemosynthetic ecosystems and far-field transport into the ocean interi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Accounting for errors in the dissolution rate (up to approximately one order of magnitude), this lifetime is far shorter than particle settling times expected for nanoparticulate material, which, through Stokes Law, equates to 0.18 m/year for a 100-nm FAP particle. By analogy to other nanoparticulate phases identified in modern hydrothermal plumes ( 63 ), these particles would be expected to reside in the oceanic water column for several years and, more likely, decades. Thus, we conclude that the preservation of FAP particles implies that seawater was at or above saturation with respect to FAP to arrest the thermodynamic drive for dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Accounting for errors in the dissolution rate (up to approximately one order of magnitude), this lifetime is far shorter than particle settling times expected for nanoparticulate material, which, through Stokes Law, equates to 0.18 m/year for a 100-nm FAP particle. By analogy to other nanoparticulate phases identified in modern hydrothermal plumes ( 63 ), these particles would be expected to reside in the oceanic water column for several years and, more likely, decades. Thus, we conclude that the preservation of FAP particles implies that seawater was at or above saturation with respect to FAP to arrest the thermodynamic drive for dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…While the source of Mn in the Caribbean waters is not well‐constrained, emerging evidence from seafloor hydrothermal vents indicates that high concentrations of dissolved‐Mn(II) and Mn(III) in ocean waters and Mn‐oxide deposits are mainly related to hydrothermal activities (Middag, de Baar, Laan, & Klunder, 2011). Mn(II) in hydrothermal plumes may have longer oxidation half‐lives than much of the other trace metals (e.g., iron, copper, zinc) dispersing over a distance of more than 4,000 km from the vent (Gartman & Findlay, 2020; Resing et al., 2015; Yücel et al., 2021). Being surrounded by the Lesser Antilles Volcanic Arc (LAVA) in the east, and the Central American Volcanic Arc (CAVA) in the west, the Caribbean Sea may receive Mn from volcanic sources (Homoky et al., 2011) and hydrothermal inputs (Frank et al., 2006) (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxide and sulfide nanocolloids are abundant on Earth and can be found in diverse habitats, including soils, water, rocks and living organisms ( Cornell and Schwertmann, 2003 ; Jolivet et al, 2006 ; Rickard and Luther, 2007 ; Sagnotti, 2007 ; Navrotsky et al, 2008 ; Konishi et al, 2012 ; Guo and Barnard, 2013 ; Posth et al, 2014 ; Maher, 2016 ; Claudio et al, 2017 ; Yuan et al, 2020 ; Huang, 2022b ). These encompass diverse environments such as high pH hydrothermal vents ( Lough et al, 2019 ; Yücel et al, 2021 ), ice sheets ( Hawkings et al, 2014 ), fly ash and street dust ( Yang et al, 2016b ; Gonet and Maher, 2019 ). Remarkably, they are also found in magnetosomes from Magnetotactic Bacteria (MTB) ( Pósfai et al, 2013 ; Uebe and Schüler, 2016 ; Goswami et al, 2022 ), as well as in other biogenic iron minerals ( Posth et al, 2014 ).…”
Section: The Relevance Of Inorganic Oxidoreductase Activity In Biolog...mentioning
confidence: 99%
“…These nanocolloids form through various mechanisms ( Guo and Barnard, 2013 ), resulting in a range of sizes, shapes, and structures ( Xie et al, 2018 ). Iron sulfide nanocolloids are prevalent in hydrothermal vent plumes ( Findlay et al, 2019 ; Yücel et al, 2021 ) and can be found in many marine sediments ( Rickard and Luther, 2007 ; Gu X. et al, 2020 ; Subramani et al, 2020 ). Geological evidence indicates that secondary pyrrhotite, pyrite, greigite, mackinawite and green rust (fougerite) may have existed as nanocolloids during the Hadean and early Archean era, a time period that predates and overlaps with the emergence of proteins and primitive life forms ( Holland, 2007 ; Raiswell and Canfield, 2012 ; Bekker et al, 2013 ; Catling, 2013 ; Halevy et al, 2017 ; Goswami et al, 2022 ).…”
Section: The Relevance Of Inorganic Oxidoreductase Activity In Biolog...mentioning
confidence: 99%